Desarrollo y simulación del proceso de producción de mezcal. Alternativa tecnológica para los productores michoacanos - Martínez Corona, René Leobardo (Universidad Michoacana de San Nicolás de Hidalgo, 2013)
Michoacan is a Mexican state with an extensive production of mezcal and mezcal agave, their preparation is made in a traditional way, with an average production of 300,000 L/year. After 10 years of political efforts to include 29 Michoacan municipalities within the declaration "Denominación de Origen de Mezcal” (Mezcal Protected Designation of Origin), finally this goal was achieved recently; thereby producing municipalities will benefit greatly. In order to achieve the scaling of the process from a crafted level to an industrial scale, this work takes advantage of SuperPro Designer® and Aspen Plus® simulators. The knowledge about unit operations, process equipment, and material types, the ancestral experience and the scientific research previously developed by the states within the Mezcal PDO are also considered. The methodology consisted in the establishment of each stage from the production process: cooking, crushing, fermentation and distillation using mezcal agave as raw material in the SPD ® simulator, which, by its modular nature, allows the use of equipment for the representation of the unitary operations that are not included within the software. On the other hand, the distillation was performed on Aspen Plus® v.7.2, because SPD® v.8.0 has no interaction parameters for the compounds present in the "Mosto Muerto" (which is the name the producers give to fermented juice from agave), that are necessary in the NRTL thermodynamic model for calculating the VLE. Temperature, time batch and configuration of the process steps were determined by sensitivity studies performed on simulators. Using these variables, it was possible to obtain 1.890 L of mezcal 50.5%V from 10,000 kg of mezcal agave with 22% m/m of reducing sugars. The present investigation is a very important tool for Michoacan producers, which will enable them to know their processes, to implement processing technologies, to technify the crafted production, to observe the NOM-070 requirements, to improve their yields and to obtain a product with constant organoleptic characteristics. Certainly, all those things will allow them to compete in the national and international market.

Michoacán es un estado con vasta producción de agave mezcalero y mezcal, su obtención se efectúa de manera artesanal, produciéndose 300,000 L/año. Después de 10 años de gestión se incluirán a 29 municipios del estado en la declaratoria “Denominación de Origen Mezcal” beneficiándose de ésta. Para lograr el escalamiento de la fabricación artesanal a la producción industrial esta investigación toma como base los simuladores SuperPro Designar® y Aspen Plus ®, así como el conocimiento de las operaciones unitarias, equipos de procesamiento, tipos de materia prima, experiencia ancestral e información científica realizada por los estados que conforman la denominación antes mencionada. La metodología consistió en establecer cada una de las etapas del proceso de producción: cocción, molienda, fermentación y destilación; utilizando agave mezcalero como materia prima en el simulador SPD®, que por su naturaleza modular permitió el empleo de equipos para la representación de las operaciones unitarias que no están incluidas dentro del software, mientras que la destilación se realizó en Aspen Plus® v.7.2 debido a que SPD® v.8.0 no cuenta con los parámetros de interacción de los compuestos presentes en el mosto muerto necesarios para el modelo termodinámico NRTL en el cálculo del ELV. Se determinó la temperatura, tiempo de lote y configuración de las etapas del proceso mediante estudios de sensibilidad realizados en los simuladores, variables con las que se obtuvieron 1,890 L de mezcal 50.5 %V a partir de 10,000 kg de agave mezcalero con 22% m/m de azúcares reductores. La presente investigación es una herramienta de gran importancia para que los productores michoacanos, conozcan sus procesos, implementen tecnologías de procesamiento, tecnifiquen su fabricación artesanal, cumplan con los requerimientos de la NON-070, mejoren los rendimientos y obtengan un producto con características organolépticas constantes que les permita competir con el mercado nacional e internacional.
Facultad de Ingeniería Química. Maestría en Ciencias en Ingeniería Química
Keywords: info:eu-repo/classification/cti/7; FIQ-M-2013-0182; Simulación; Proceso; Producción de mezcal; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4832